A laser-shock-enabled hybrid additive manufacturing strategy with molten pool modulation of Fe-based alloy. (October 2022) - Liu, Jian; Zhao, Shusen; Zhang, Xiaohan; Lin, Xuechun; Hu, Yaowu
Abstract: A novel hybrid laser additive manufacturing (LAM) process based on laser shock modulation of molten pool (LSMMP) is proposed in this work. By using a combination of experiment and simulation, the residual stress, heat transfer, and mass transfer behaviors are comprehensively studied. Also, microstructure evolution behavior is analyzed. The relationship between the convection behavior, the evolution of microstructure and the enhancement of residual stress induced by LSMMP is established. Compared with the traditional post-treatment process, the LSMMP assisted LAM process exhibits higher efficiency in residual stress control with the same pulsed laser energy input. The hidden mechanism in microstructure evolution and residual stress enhancement is expected to be possible related to intensified molten pool convection, uniform solute distribution and improved cooling rate induced by LSMMP. The hybrid LAM process strategy based on LSMMP provides a new approach for the application of short pulse laser in hybrid manufacturing.